Security Guarantee Midwife in Conflict Areas - Rochma Putri, Ika Nanda; Afifah, Wiwik (Jurnal Hukum Magnum Opus, 2024)
The background of this research is that health services are a state obligation as mandated by the Constitution of the Republic of Indonesia of 1945. These services must be distributed evenly across all regions of Indonesia, not just focused on the island of Java. Indonesia includes 3T areas (Disadvantaged, Frontier, Outermost) which face numerous issues, one of which is social conflict. These areas are particularly prone to social conflict, which can hinder the delivery of health services provided by the state. As part of the health service assistance, the state deploys health workers according to the Ministry of Health's Nusantara Sehat program, including midwives. In some 3T areas, social conflict poses threats to midwives, sometimes resulting in their injury or death. Therefore, ensuring the safety of midwives is crucial for improving health services throughout Indonesia and protecting the rights of midwives working in these regions. This research aims to explore, understand, and explain the security guarantees for midwives in 3T areas experiencing social conflict. The research employs a normative juridical method with a statutory and conceptual approach. The findings indicate that current laws and regulations do not clearly define the security guarantees that midwives should receive when working in conflict zones.